MENINGKATKAN KEMAMPUAN PENGURANGAN MELALUI MEDIA INTELLIGENCE STICK BAGI MURID DENGAN DISABILITAS INTELEKTUAL RINGAN - Agita Hendini; Mega Iswari; Antoni Tsaputra; Yosa Yulia Nasri (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2026)
This study aimed to improve the subtraction skills of a sixth-grade student with a mild intellectual disability at SLBN 1 Payakumbuh in solving two-digit subtraction problems requiring the borrowing technique, utilizing